Audio-Visual versus Lecture Education on Teaching Quality and Discharge Readiness in Cataract Patients - Nasrulloh, Iqbal; Nursiswati, Nursiswati; Ibrahim, Kusman (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Cataract surgery in a day-care unit significantly reduces preoperative education time, posing a challenge for elderly patients with cognitive decline. Traditional lectures rely on nurse availability and verbal recall, necessitating a more standardized and sensory-engaging alternative. This study compared the effectiveness of audio-visual media versus traditional lectures on the Quality of Discharge Teaching (QTDS) and Readiness for Hospital Discharge (RHDS) in phacoemulsification patients. A quasi-experimental, post-test-only study was conducted at a tertiary referral hospital in August 2023. Using sequential sampling, 100 participants were allocated to either the lecture group (n=50) or the audio-visual group (n=50) based on a systematic time-based approach (odd-even surgery dates) to prevent cross-contamination. Data were collected through the validated Indonesian P-QTDS and P-RHDS questionnaires and analyzed using the Mann–Whitney U test. No significant difference was found in teaching quality (p=0.647), with both methods rated as satisfactory. However, the audio-visual group had a higher mean rank for discharge readiness (55.47) than the lecture group (45.53). Although approaching marginal significance (p=0.073), this reflects a clinically meaningful trend favoring the audio-visual intervention. The use of audio-visual media is recommended as the primary educational method to improve discharge readiness and ensure nursing standardization in high-volume day-care units.